Physiological Relevance of Reciprocity between Testosterone Retention Mechanism and Androgen Binding Protein Expression in Sertoli Cells to Male Fertility: A Biochemical Perspective - Manjeet Kaur Gill-Sharma (Contemporary Research and Perspectives in Biological Science Vol. 8, 2025)
Male Infertility and Contraception present issues that await elucidation. Therefore, it becomes imperative to delineate the underlying biochemical mechanism(s) involved in maintaining elevated physiological intratesticular testosterone levels (iT). Testosterone is the principal sex-steroid hormone required for Spermatogenesis. Low iT levels invariably underlie male Infertility and failure of hormonal contraception. Lacunae pertaining to iT sequestration and the mechanism through which T brings about the stage-specific differentiation of germ cells lacking androgen receptors (AR), remain to be elucidated. Testosterone, a highly anabolic steroid with a rapid tissue clearance rate, is the intratesticular substrate that synthesizes dihydrotestosterone (DHT) for AR+ (androgen receptor) Sertoli cells and estradiol (E2) for ER + (estrogen receptor) Germ cells, implicated in Spermatogenesis. Therefore, it becomes important to delineate the biochemical mechanism(s) involved in the sequestration and retention of iT. Testosterone and ABP share an interdependent relationship. Autophagic clearance of ABP is negatively regulated by T. ABP is essential not only for maintaining high iT levels but also solubilizing it for nuclear functions, besides chaperoning its transit to Epididymides for gamete maturation. In view of the reported global decline in sperm count and catastrophic decline in male fertility, in-depth studies are necessary to understand the biochemical role of Androgen Binding Protein(s) in sequesteration, retention, bioavailability of iT/iD (intratesticular DHT)/ iE (intratesticular Estradiol) and epididymal T transport. The appropriate approach to overcome the lacunae would be the development of mice lacking functional testicular androgen-binding protein (ABPKO) with normal levels of Gonadotrophins and sex steroid hormones. Insights gained about androgen retention mechanism(s) from the ABPKO murine model will be of immense help in improving the methodologies of male fertility management.